PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT.PRIMAFOOD INTERNASIONAL CABANG KABUPATEN TANGERANG - Septiani, Indi; Mulyadi Mulyadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of work environment and work motivation on employee performance at PT.Primafood Internasional, Tangerang Regency branch. The research method used in this study is quantitative. The population used in this study is employees of PT Primafood Internasional, Tangerang Regency branch. The sampling method used by the author in this study is a saturated sample method, which consists of 72 employees. The data analysis used includes regression analysis, correlation test, determination test, partial test, and simultaneous test. The results of the study show that the Work Environment Variable (X1) has a significant effect on the Employee Performance Variable (Y) with the Regression Equation Y = 18.511 + 0.563X1. The Work Motivation Variable (X2) has a significant effect on the Employee Performance Variable (Y) with the regression equation Y = 15.892 + 0.626X1. The simultaneous results show that the Work Environment Variable (X1) and Work Motivation (X2) significantly influence Employee Performance (Y) with the regression equation Y = 15.158 + 0.288X1 + 0.356X2, with a coefficient of determination of 0. 507, it can be concluded that the Work Environment (X1) and Work Motivation (X2) variables influence Employee Performance (Y) by 0.507 × 100% = 50.7%, while the remaining (100-50.7%) = 49.3% is influenced by other variables not included in the study. In the simultaneous test (F-test), the value obtained was 35.515 > 3.130, which is further supported by the p-value < Sig. 0.050 or (0.000 < 0.050). Therefore, H0: p3 = 0 is rejected, and Ha: p3 ≠ 0 is accepted. The results indicate that there is an influence of the work environment and work motivation on employee performance at PT.Primafood International's branch in Tangerang Regency.